Study and analysis on lighting energy management for highway - Suntiti, Yoomak; Atthapol, Ngaopitakkul (My University, 2018)
This paper focuses on the impact of LED luminaire in terms of illuminance and energy consumption for roadway lighting system. The comparison between HPS and LED luminaires in terms of illuminance and uniformity with the standards of Department of Highways of Thailand is presented with DIALux program. In addition, the arrangement of roadway lighting pole in case of without and with isle including the different polar distribution curves of LED luminaire is also considered and compared. The objective of this paper is to study and propose the improvement of installation with LED luminaire for roadway lighting system in terms of illuminance and uniformity using the mounting height adjustment method and the pole spacing adjustment. The results show that, by focusing on average illuminance and uniformity, the type of polar distribution curve and the adjustment of pole spacing of lighting pole can significantly improve the installation of LED luminaire for roadway lighting and it will be useful in the installation of LED luminaire for roadway lighting in the future.
Keywords: DIALux; Energy savings; HPS luminaire; Illuminance; LED luminaire; Roadway lighting; Uniformity